Comparative effectiveness of multiple different non-pharmacologic interventions for post-stroke constipation: a Bayesian network meta-analysis - Feng, Sisi; Wu, Xinhui; Dai, Xuemei; Liu, Zhihao; Luo, Yi; Wang, Fei (Frontiers in Neurology, 2025)
BackgroundPost-stroke constipation (PSC) is a common complication among stroke patients, with a positive correlation to stroke severity. Straining during defecation in constipated patients can increase intracranial pressure, posing a high risk for secondary strokes, negatively impacting prognosis, disease progression, and contributing to the development of depression and anxiety. Non-pharmacological interventions (NPIs), including traditional Chinese medicine (TCM) and rehabilitation approaches, have been explored due to challenges in advancing Western medical treatments. However, the optimal treatment remains unclear, necessitating guidance for clinical practice. This research employs Bayesian network meta-analysis (NMA) to identify the most effective NPIs for improving clinical outcomes and alleviating constipation in post-stroke patients.MethodsWe conducted a NMA of randomized controlled trials to evaluate the relative efficacy of eight NPIs for PSC: acupuncture therapy (AT), acupoint catgut embedding (ACE), auricular therapy (ART), moxibustion (MT), abdominal massage (AM), point application (PA), physiotherapy (PT), and cognitive behavioral therapy (CBT). The primary outcome was the clinical effective rate (CER), and the secondary outcome was the Constipation Scoring System (CCS). To establish a comparative hierarchy of interventions, surface under the cumulative ranking curve (SUCRA) values were calculated, representing the probability of relative efficacy across treatments.ResultsA comprehensive literature review identified 53 clinical studies with 5,813 participants to evaluate the relative efficacy of eight NPIs. ACE ranked highest for both CER and CCS (SUCRA = 94.7, 97.8%), followed by PT (88.4, 81.7%). In contrast, ART and AM ranked lower, indicating relatively less efficacy compared with other interventions.ConclusionAcupoint catgut-embedding (ACE) may represent a potentially superior non-pharmacological intervention for improving clinical outcomes and reducing constipation severity in post-stroke patients. Physiotherapy (PT) also demonstrated favorable efficacy, ranking second in both clinical outcomes. However, further high-quality, multicenter clinical trials are needed to validate and refine these findings.